TUMEFACTIVE REBOUND OF MULTIPLE SCLEROSIS FOLLOWING CESSATION OF FINGOLIMOD. Issue 12 (15th November 2016) - Salam, Sharfaraz; Dunbar, Daniel; Lavin, Tim; Pace, Adrian; Mihalova, Tatiana
Abstract : Fingolimod is an oral sphingosine-1-phosphate receptor modulator approved for the treatment of active relapsing remitting multiple sclerosis (RRMS). Recent reports have highlighted the possible risk of rebound disease activity after withdrawal of fingolimod. We describe a patient who developed severe tumefactive MS on discontinuing fingolimod treatment. A 32-year old female with RRMS with ongoing relapses escalated treatment from interferon-beta to fingolimod. Pre-treatment, she was JC-virus positive with high titers of 2.41. She developed side effects and persistent lymphopenia. Fingolimod was reduced to alternate day dose. She then complained of worsening memory and cognition, raising concern of PML. MRI with contrast showed ongoing MS disease activity, but no sign of PML. We planned to switch her to alemtuzumab. She discontinued fingolimod in May 2015. By July all side effects resolved. She started low dose naltrexone therapy and now declined alemtuzumab. In August she presented acutely with tetraparesis, swallowing, balance and memory difficulties. MRI images demonstrated severe rebound inflammatory disease with numerous contrast-enhancing tumefactive lesions. She was treated with intravenous steroids and alemtuzumab leading to partial neurological recovery after 6 months. Rebound MS disease following discontinuation of fingolimod presumably reflects the cessation of autoreactive lymphocyte sequestration in peripheral lymph nodes after drug washout. Early replacement with alternative immunomodulatory agents should be planned to minimize the risk of this serious complication.